The Genus Licuala Wurmb (Arecaceae) in Java - Siregar, Etti Sartina; Tjitrosoedirdjo, Sri Sudarmiyati (Jurnal Natur Indonesia, 2011)
The comprehensive revision of the genus has been done in the Malay Peninsula, New Guinea, Sumatra andKalimantan. In Java, the revision of Licuala has never been recently completed. This study was based onmorphological characters of specimens which are preserved in Herbarium Bogoriense. The several living collectionscultivated in Bogor Botanical Garden were studied. The aim of this study is to ascertain the correct names andimprove the species delimitation of Licuala in Java. The result shows that there are three species of Licuala inJava. They are L. gracilis, L. pumila and L. spinosa. Two previously known species have been placed into synonymies;L. flabellum to L. gracilis, and L. spectabilis to L. spinosa. Licuala gracilis is endemic for west Java.